The Early Developmental Outcomes of Prenatal Alcohol Exposure: A Review - Subramoney, Sivenesi; Eastman, Emma; Adnams, Colleen; Stein, Dan J.; Donald, Kirsten A. (Frontiers in Neurology, 2018)
Aim: This paper systematically reviews the literature on the effects of prenatal alcohol exposure on early child development from birth to 5 years with the aim to synthesize the developmental outcomes associated with prenatal alcohol exposure, and inform further research to improve our knowledge of the manifestations of prenatal alcohol exposure. Methods: Electronic databases (MEDLINE, Psych INFO, and Psych ARTICLES) were searched to find papers on the developmental outcomes of prenatal alcohol exposure in neonates, infants and toddlers and pre-school aged children. Studies were selected based on participants self-reporting alcohol consumption during pregnancy (either prospectively or retrospectively) and/or children being diagnosed with FASD based on a standardized assessment that includes a dysmorphology examination. The search was limited to peer-reviewed, English language studies involving human subjects, up to 5.5 years old. Results: Out of the 1684 titles screened, a total of 71 papers were identified as relevant and included in this review. The majority of studies were prospective longitudinal studies. A range of assessment modalities (or tools) was used to determine neurodevelopmental outcomes of prenatal exposure to alcohol in the age group under review, the most frequently described being the Bayley Scales of Infant and Toddler Development (BSID) (n = 19). Studies varied in terms of the dose, frequency, and timing of alcohol consumption during pregnancy and methodology used to assess alcohol consumption. Findings demonstrate extensive evidence for poor global developmental outcomes in children prenatally exposed to alcohol, particularly with moderate to severe levels of prenatal alcohol exposure. Conclusion: The outcomes related to lower levels of prenatal alcohol exposure as well as outcomes in specific developmental domains, are poorly understood. Further research should aim to clarify the more subtle or less easily measurable manifestations of prenatal alcohol exposure on early development when the potential for greatest impact of interventions is highest.